MONTE CARLO ANALYSIS OF FETAL DOSE DISTRIBUTION IN PREGNANCY FOR DIFFERENT FETAL AGES, BEAM LOCATION, BEAM ENERGY, AND FIELD SIZES - Nikmah, Khusniatun; Ramadhan, Muhammad Vitro; Sumaryada, Tony; Rhani, Muhammad Fahdillah; Husin, Abd. Djamil; Yani, Sitti (Indonesian Physical Review, 2025)
Treatment with radiotherapy in pregnant women may occur due to some critical conditions. The dose given during the treatment process is not only received by the patient but can also be absorbed by the fetus which can affect its growth. Moreover, the radiation target is near the fetus such as the lung. This study aims to determine the dose distribution to the fetus with variations in fetal age (trimester 1, 2, and 3), beam energy, field size, and fetal distance to the target location (lung). The entire simulation utilized the Monte Carlo-based software EGSnrc-DOSXYZnrc which produced a 3-dimensional dose distribution on the virtual phantom. The simulated virtual phantom is a box with a size of 40×40×40 cm3 containing several materials, namely water, tissue, and lung. The size of the fetus is varied according to trimesters 1, 2, and 3. The beam is in the form of monoenergetic photons with energies of 3 MeV and 5 MeV emitted from above with a source to surface distance (SSD) of 48 cm. The field size was set at 5×5 cm2 and 8×8 cm2 on the phantom surface. The beam axis was located at a distance of 5 cm and 3 cm from the fetus. The results showed that the four variations performed affected the fetal dose, where the fetal dose increased considerably when the field size was enlarged and the beam axis was closer to the fetal position. The increase in fetal dose is also influenced by the increase in fetal age and beam energy. Meanwhile, the location of the beam below the lung causes an increased dose to the fetus due to the closer position of the beam to the fetus.